-4-3n+3=23

Simple and best practice solution for -4-3n+3=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-3n+3=23 equation:


Simplifying
-4 + -3n + 3 = 23

Reorder the terms:
-4 + 3 + -3n = 23

Combine like terms: -4 + 3 = -1
-1 + -3n = 23

Solving
-1 + -3n = 23

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -3n = 23 + 1

Combine like terms: -1 + 1 = 0
0 + -3n = 23 + 1
-3n = 23 + 1

Combine like terms: 23 + 1 = 24
-3n = 24

Divide each side by '-3'.
n = -8

Simplifying
n = -8

See similar equations:

| x=218+508 | | 3.6/y=10.8/12 | | 30.99-25= | | 5(8x-8)=440 | | 11-8x=1-6x | | 3(5y-4)+15=5(y-3)-(3y+2) | | 12+3x=24-3x | | -20m+20=-17m-13 | | 20=12x+3 | | 5/6=x/6 | | 9x+(-7)=8x | | 10c=-11-3(-3c+1) | | -8r=-3r+20 | | x/6=0,5 | | 14v-12+7w+(-4v)= | | 20-y+20=2y-20 | | 6-0.5x=15 | | 9x+(17)=8x | | 8h+8=4h | | 18.75=3u | | 459.90=210x+1.19x | | 4=29+13x | | 6c=-8+2c | | -16-6-2g=-4(-g-20) | | y+3y-1=y | | -3g+4=9-8g | | 7x-x-10=-4 | | F(-4)=3x^2+5 | | 459.90=210x+119x | | 3=9+4c | | 14v+(-4v)= | | 5-2+8v=-9-4v |

Equations solver categories